Evaluate the integral below.
∫ − ∞ ∞ 1 + x 2 1 d x
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We will first prove that:
∫ 1 + x 2 1 d x = t a n − 1 ( x ) + C
If we define f(x) as:
d x d t a n ( x )
Then by the inverse function rule:
d x d t a n − 1 ( x ) = f ( t a n − 1 ( x ) ) 1
By the quotient rule:
f ( x ) = d x d c o s ( x ) s i n ( x ) = c o s 2 ( x ) c o s 2 ( x ) − ( − s i n 2 ( x ) ) = c o s 2 ( x ) 1 = s e c 2 x
It follows that:
d x d t a n − 1 ( x ) = s e c 2 ( t a n − 1 ( x ) ) 1 = 1 + t a n 2 ( t a n − 1 ( x ) ) 1 = 1 + x 2 1
Now that we have determined the indefinite integral:
∫ − ∞ ∞ 1 + x 2 1 d x = ( l i m x → ∞ t a n − 1 ( x ) ) − ( l i m x → − ∞ t a n − 1 ( x ) ) = 2 π − 2 − π = π
Upon first inspection of the integral, we notice that this is a definite integral form of the identity ∫ 1 + x 2 1 d x = a r c t a n ( x ) However, because the bounds are infinities, this definite integral is improper and therefore must be evaluated via limits ⇒ lim t → ∞ ∫ − t t 1 + x 2 1 d x ⇒ lim t → ∞ arctan ( t ) − arctan ( − t ) = 2 π + 2 π = π
Problem Loading...
Note Loading...
Set Loading...
I = ∫ − ∞ ∞ 1 + x 2 1 d x = 2 ∫ 0 ∞ 1 + x 2 1 d x = 2 ∫ 0 2 π 1 + tan 2 θ sec 2 θ d θ = 2 ∫ 0 2 π d θ = 2 θ ∣ ∣ ∣ ∣ 0 2 π = π Since the integrand is even. Let x = tan θ ⟹ d x = sec 2 θ Note that 1 + tan 2 θ = sec 2 θ